Structural analysis and treatment of acute liver injury of polysaccharides from the Radix Actinidiae Chinensis - Ding, Zhongpeng; Ying, Qianyi; Lei, Jing; Zhang, Ningchen; Xia, Yu; Du, Yilin; Xu, Beihua; Shi, Senlin (Frontiers in Pharmacology, 2025)
ObjectiveTo investigate the therapeutic effects of the PRAC on acute liver injury and its potential as an ingredient in drugs and nutraceuticals.MethodsMicrowave-assisted extraction technology combined with Box-Behnken model combined with the three kinds of artificial neural networks was used to optimize PRAC extraction process. Characterize the structure and composition of PRAC. In order to prevent PRAC from being degraded by the gastrointestinal environment, PRAC-loaded liposomes were fabricated. The efficacy of PRAC-loaded liposomes was evaluated by three acute liver injury animal models prepared according to different mechanisms.ResultsThe best yield of PRAC was 4.49%, and the purity reached up to 86.53% by optimizing the microwave parameters using Box-Behnken model combined with the three kinds of artificial neural networks. PRAC was characterized as a galactan having a backbone consisting predominately of →4)-D-Galp-(1→ and →4)-D-Glcp-(1→ with a molecular weight of 12.713 kDa. The PRAC-loaded liposome obtained had a size about 340 nm with a polydispersity index 0.234. The entrapment efficiency was 70.12% and the drug loading was 1.24%. Liposomes can be fully released in the gastrointestinal environment within 12 h and have long-term stability at 4°C. The therapeutic effect of PRAC liposomes on acute liver injury was confirmed by three animal models of acute liver injury.ConclusionPRAC is a potential drug for the treatment of acute liver injury.